Development of Translational Methods in Spectral Analysis of Human Infant Crying and Rat Pup Ultrasonic Vocalizations for Early Neurobehavioral Assessment - Zeskind, Philip S.; McMurray, Matthew S.; Garber, Kristin A.; Neuspiel, Juliana M.; Cox, Elizabeth T.; Grewen, Karen M.; Mayes, Linda C.; Johns, Josephine M. (Frontiers in Psychiatry, 2011)
The purpose of this article is to describe translational methods by which analyses of crying in young human infants and ultrasonic vocalizations of rat pups can be used to assess effects of adverse prenatal conditions on early neurobehavioral integrity. Whereas the long history of analyses of human infant crying has developed a rich set of measures that are sensitive to neurobehavioral insult, analyses of rat pup vocalizations allow for strict controls over the prenatal conditions that may adversely affect neurobehavioral development. The development of translational methods will allow for findings in respective fields of inquiry to inform one another. To this end, we present an enhanced taxonomy of a novel set of common measures of crying in both human infants and rat pups based on the conceptual framework that infant crying is a graded and dynamic acoustic signal. This set includes latency to vocalization onset, duration and repetition rate of expiratory components, duration of inter-vocalization-intervals and spectral features of the sound, including the frequency and amplitude of the fundamental and dominant frequencies. We also present a new set of classifications of rat pup USV waveforms that include qualitative shifts in fundamental frequency, similar to the presence of qualitative shifts in fundamental frequency that have previously been related to insults to neurobehavioral integrity in human infants. Challenges to the development of translational analyses, including the use of different terminologies, methods of recording and spectral analyses are discussed, as well as descriptions of automated processes, software solutions and pitfalls.